Incidence and management of wheat seed borne fungi collected from Baghlan Province, Afghanistan - MOMINZAI, MUHAMMAD AJAN; RAHMATZAI, NAJIBULLAH; KAMIL, DEEBA; SAHARAN, MAHENDER SINGH (The Indian Journal of Agricultural Sciences, 2023)
To identify the association of seed borne fungi in wheat seed samples (20 wheat genotypes collected from 11 different districts of Baghlan province), the standard blotter method was used. Thirteen seed borne fungi, viz. Alternaria alternata, Bipolaris spp, Gibberella zeae, Curvularia lunata, Rhizopus stolonifer, Aspergillus flavus, A. niger, Penicillium spp, Cladosporium cladosporioides, Acremonium spp, Ulocladium spp, Arthrobotrys oligospora and Tilletia indica were observed from the seeds. Nine wheat varieties collected from Zonal Agricultural Research Station, Baghlan, Afghanistan were analyzed for the association of seed borne fungi. Ten fungi, viz. A. alternata, Acremonium spp, Cladosporium cladosporioides, Ulocladium spp, Curvularia lunata, Bipolaris spp, Gibberella zeae, A. flavus, A. niger and Penicillium spp. were recorded. Among them A. alternata and Bipolaris spp. were predominant in most of the seed samples. Minimum per cent infection of 1.33% was recorded with treatment having Ridomil @2.5 g/kg seed whereas maximum seeds infection of 52% was recoded in control. Present study revealed the occurrence of seed borne fungi in different wheat genotypes in Baghlan province of Afghanistan. Studies helped in identifying suitable fungicides and bioagents for managing seed borne fungi in wheat.